2002
DOI: 10.1034/j.1600-0676.2002.220102.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel role of alkaline phosphatase in protection from immunological liver injury in mice

Abstract: The development of liver injury may lead to a dysfunction in AP synthesis and release. Levamisole may make normal hepatocytes, like the hepatocytes from liver-injured mice, highly sensitive to lipopolysaccharide through inhibiting AP synthesis. The findings obtained in this study suggest that AP may contribute to protection from injury by a mechanism involving neutralization of endotoxin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…After exposure to LPS both in vitro and in vivo, hepatocellular damage was increased when AP synthesis was inhibited. It was suggested that high levels of AP exert a protective effect against liver damage by neutralizing endotoxin (33). In the present study, this protective effect was observed in the prophylaxis group but not in the early treatment group.…”
Section: Discussionsupporting
confidence: 68%
“…After exposure to LPS both in vitro and in vivo, hepatocellular damage was increased when AP synthesis was inhibited. It was suggested that high levels of AP exert a protective effect against liver damage by neutralizing endotoxin (33). In the present study, this protective effect was observed in the prophylaxis group but not in the early treatment group.…”
Section: Discussionsupporting
confidence: 68%
“…Enhanced TNAP levels have been observed in leukocytes from patients with Gram-negative sepsis (Chikkappa 1992). Administration of lipopolysaccharide (LPS)-a constitutent of the outer membrane of Gram-negative bacteria-induced systemic up-regulation of TNAP (Xu et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Although inhibition of endogenous alkaline phosphatase synthesis has been shown to increase hepatic injury after LPS challenge 39 , endogenous alkaline phosphatase probably played only a minor role in the present study. Plasma alkaline phosphatase activity did not increase significantly after I/R throughout the reperfusion phase.…”
Section: Hepatic and Pulmonary Histopathologymentioning
confidence: 92%